491 Efficacy of FT218, a Once-Nightly Sodium Oxybate Formulation, by Narcolepsy Subtype: A Post Hoc Analysis From the REST-ON Study. (3rd May 2021) - Roy, Asim; Morse, Anne Marie; Dubow, Jordan; Seiden, David; Bogan, Richard
Abstract: Introduction: FT218 is an investigational, once-nightly, controlled-release formulation of sodium oxybate for the treatment of narcolepsy. The purpose of this post hoc analysis of the REST-ON study was to evaluate the effect of FT218 on measures of excessive daytime sleepiness (EDS) in patients with narcolepsy subtypes 1 (NT1) and 2 (NT2). Methods: This was a randomized, double-blind, placebo-controlled, multicenter study in patients with narcolepsy ≥16 years old. Patients were stratified by narcolepsy subtypes and randomized 1:1 to receive FT218 or matching placebo: 4.5 g/night for 1 week, 6.0 g/night for 2 weeks, 7.5 g/night for 5 weeks, and 9.0 g/night for 5 weeks (maximum treatment duration, 13 weeks). Assessments of EDS included mean sleep latency (minutes) on maintenance of wakefulness test (MWT) and Clinical Global Impression-Improvement (CGI-I) in sleepiness. Results: A total of 190 patients were included in the modified intent-to-treat population (NT1: FT218, n=72; placebo, n=73; NT2: FT218, n=21, placebo, n=24). Patients with NT1 or NT2 receiving FT218 had significant improvement in MWT. LS mean difference in mean sleep latency (minutes) vs placebo for NT1 was 5.97 for 9.0 g (week 13), 7.02 for 7.5 g (week 8), and 4.89 for 6.0 g (week 3; all P<0.001), and for NT2, 6.27 for 9.0 g (P=0.020), 4.01 for 7.5 g (P=0.162), and 5.33 for 6.0 g (P=0.020). A higher proportion of NT1 patients receiving FT218 had significant improvement on CGI-I vs placebo (9.0 g: 75.5% vs 35.9%; 7.5 g: 66.9% vs 27.9%; 6.0 g: 39.9% vs 7.8%; all P<0.001). A higher number of NT2 patients receiving FT218 were consistently rated as much/very much improved vs placebo, based on descriptive statistics. FT218 was generally well tolerated. Conclusion: FT218 had similar efficacy on EDS at evaluated doses in NT1 and NT2, with improvement in MWT and CGI-I greater than placebo. FT218 may provide effective treatment for EDS in patients with narcolepsy, with or without cataplexy. Support (if any): Avadel Pharmaceuticals.